'I like knowing when the zombies arrive, I won't be naked': Young women and leisure handcrafting in the United States. Issue 1 (1st March 2018) - Stalp, Marybeth C.; Gardner, Emily A.; Beaird, Ashley
In a modern world where technology is readily available, handwork is sometimes taken for granted, hidden or viewed with suspicion by outsiders, without fully understanding the benefits of engaging in such mindful activity. Younger women face challenges of trying to fit into a hobby subculture that is stereotypically reserved for older women (45 years and older). In-person and online qualitative research with 32 young women leisure crafters (aged 18–44 years) attest to some of the difficulties of trying to engage in time- and labour-intensive creative activities. In this research, we demonstrate that young women rely on both traditional and new ways of learning creativity; they resist consumer culture to learn handcrafting practices; they have to negotiate space and time to engage in craft; and they find themselves defending their choices of handcrafting as young women.